Applications of bioactive compounds of traditional Chinese medicine in breast cancer management - Srivastava, Saumya; Upadhye, Vijay Jagdish; Prasad, Madhulika Esther; Singh, Pallavi (Creative Pharma Assent, 2025)
Background: Over the past few decades, the prevalence of breast cancer has been rapidly increasing, making it one of the most prevalent malignancies diagnosed in women globally. Traditional Chinese Medicine (TCM) has gained attention as a potential approach for managing breast cancer by boosting immune response, inhibiting cancer-related gene activity, and alleviating the adverse effects of radiotherapy and chemotherapy. TCM offers a valuable framework for therapeutic systems and scientific exploration that is widely practiced in many regions worldwide, primarily in China, Korea, and Japan. The herbal components of TCM exhibit complex biological activities that influence multiple aspects of cancer progression, including cell proliferation, programmed cell death (apoptosis), immune modulation, and tumor-host interactions. Methodology: A systematic literature review was conducted using peer-reviewed articles published between 2017 and 2024. Relevant data were collected from publicly available scientific databases. Non-English, Conference papers, and duplicate studies were excluded to ensure the inclusion of high-quality and relevant research findings. Result and Discussion: Analysis revealed that specific bioactive compounds in TCM exhibit significant anti-cancer effects. For example, ginsenoside Rg3 inhibited tumor growth by 45% in vivo, while curcumin reduced MDA-MB-231 breast cancer cell viability by 60% at 20 μM. Conclusion: The promise of TCM, especially its bioactive components and medicinal herbs in the treatment of breast cancer, is the main highlight of this paper. Additionally, it highlights the key scientific databases that provide critical insights into TCM research while exploring the therapeutic mechanisms of Chinese herbs and their bioactive components in mitigating breast cancer progression.